If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + 2 + 2y = 10y Reorder the terms: 2 + 4y + 2y = 10y Combine like terms: 4y + 2y = 6y 2 + 6y = 10y Solving 2 + 6y = 10y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-10y' to each side of the equation. 2 + 6y + -10y = 10y + -10y Combine like terms: 6y + -10y = -4y 2 + -4y = 10y + -10y Combine like terms: 10y + -10y = 0 2 + -4y = 0 Add '-2' to each side of the equation. 2 + -2 + -4y = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -4y = 0 + -2 -4y = 0 + -2 Combine like terms: 0 + -2 = -2 -4y = -2 Divide each side by '-4'. y = 0.5 Simplifying y = 0.5
| 2x^8+28x^7+90x^6= | | -7r-4=4+r | | 4b+20=7b+8 | | 2p-5=7+8p | | 12(2k+11)=12(2+12) | | 7x+xi-3yi=3y+9i | | 2x^3-12x^2+64=0 | | 3+2x=2x-x+4 | | y=6lnx | | (a-3)(a^2+3a+a)=0 | | 6x^3-15x^2+18x= | | x^5+x^4-14x^3-2x^2+24x=0 | | 0.95x+.05(18-x)=.10(63) | | x*.25=136 | | 5x-2+3y-6x-43-10.8x=7 | | 5x-2+3y-6x-43-10.8=7 | | 4p^2-8p-5= | | 3m-7m=p | | 12u^2-25u+12= | | 4x^2(3x^2+5x-2)=0 | | 2a^2+21a+49=0 | | 2(3x-1)=9(6x-9) | | 6.1*(3.1+2.5x)=15.3x-3.9 | | 3b^2-27b+60= | | n(2+6)= | | 4x-(2x+5[x-2(x-4)-5])=0 | | 6-4=-14 | | 2x^2+8x=-32 | | x^2+4x=90 | | 3(4+6)= | | -6-4=-14 | | 100x=0.00*50.00 |